2014
DOI: 10.5586/asbp.2001.013
|View full text |Cite
|
Sign up to set email alerts
|

Glomus arenarium, a new species in Glomales (Zygomycetes)

Abstract: A new ectocarpic arbuscular mycorrhizal fungal species, Glomus arenarium (Glomales, Zygomycetes), was recovered from maritime sand dunes of northern Poland. Glomus arenarium forms spores with a narrow and hyaline subtending hypha. Spores are orange to raw umber, globose to subglobose, (55-)97(-120) µm diam or ovoid, 65-105 x 95-140 µm. Their wall consists of three layers: a hyaline outermost layer present only in very young spores, a semiflexible, hyaline middle layer rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The last two genera were only recently described (Błaszkowski, Chwat, Góralska, Ryszka, & Kovács, 2015). These two genera were identified by their spores, and it is thus suggested that their low occurrence may be attributed to a rare or seasonally sporulation or to their delicate spores easily decomposed by other organisms (Błaszkowski, Tadych, & Madej, 2000;Błaszkowski et al, 2015;Stutz & Morton, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The last two genera were only recently described (Błaszkowski, Chwat, Góralska, Ryszka, & Kovács, 2015). These two genera were identified by their spores, and it is thus suggested that their low occurrence may be attributed to a rare or seasonally sporulation or to their delicate spores easily decomposed by other organisms (Błaszkowski, Tadych, & Madej, 2000;Błaszkowski et al, 2015;Stutz & Morton, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…observ.). on the other hand, cultivation of field soils in trap cultures may initiate sporulation of fungi forming spores seasonally, rarely or not at all in field conditions (Błaszkowski, Kovács and Balázs 2009;Błaszkowski, Tadych and madej 2000;Stutz, morton 1996). an ideal method of recognizing of amF associated with plant roots seems to be that using molecular tools.…”
Section: Acta Mycologicamentioning
confidence: 99%
“…slowinskiensis, for example, in the spore wall structure, which is two-layered in the former new AMF (Figs. 7-12), and threelayered in the three latter species (Błaszkowski et al 2001(Błaszkowski et al , 2015bBalázs et al 2015). The molecular distance between the species is also large (see the above section entitled General data and phylogeny).…”
Section: Discussionmentioning
confidence: 99%